AGE STRUCTURE AND SEX RATIO OF THRIPS Scirtothrips dorsalis HOOD (Thysanoptera : Thripidae) ASSOCIATE WITH MANGO AGROECOSYSTEM IN EAST JAVA, INDONESIA - Affandi, Affandi; dela Rosa Medina, Celia (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2013)
A research aimed to investigate the age structure and sex ratio of S. dorsalis Hood in mango agroecosystem was conducted at PT. Trigatra Rajasa farm, Situbondo, East Java, Indonesia. The research was started from April to May 2013. A Completely Randomized Design, Analysis of Variance and Least Significant Difference were used to design, knew the variance and significantly different among the treatment, respectively. Thirteen mango trees set in cross section were sampled and observed for the presence of S. dorsalis including weeds under the mango canopy and four cardinal directions of border. A weekly sample was done for four weeks. The result showed that instar one and adult were preferred to associate with weeds under the mango canopy and borders compare to mango leaves except second instar. Further, observation was presented that all the age structures were given equal male female sex ratio. Based on total population numbers, there wasnt significantly difference of age structure and sex ratio of S. dorsalis associate with weeds inside the orchard including mango leaves and borders. Twenty seven species of weeds were discovered associate with mango agroecosystem and comprehensively discused based on the most dominance and preferred by S. dorsalis. Key Words: S. dorsalis, age structure, sex ratio, mango, weeds.